The quanti-action research as a tool for teaching statistics in Basic Education - Velasque, Luciane Souza (2019)
The inclusion of a thematic section named Statistics and Probability in the BNCC to Elementary School requires reflections and experiments about how to approach the proposed contents and abilities. In this article we present the results of a "quantitative action" research carried out in a municipal public school at the Rio de Janeiro city. The project was developed with seventh grade students who actively participated in all the research stages, since the research subject choice, data collection, statistical analysis and the final research results presentation. Data collection was performed on 532 students enrolled at the school on the fundamental grade. The purpose of this article is to present a proposal on developing statistical skills through a research project. The results showed how it is feasible and motivating for students and teachers to jointly develop a research about a theme defined by the students that goes through all the stages of a research cycle.